Regional identity in Silesia (until 1526) - Mrozowicz, Wojciech (Publishing House eBooki.com.pl, 2013)
During the search for factors constituting proof of the existence of a Silesian regional identity in the Late Middle Ages, the author analyzed the process of formation and functioning of common traditions. Among the contributing factors analyzed is the name Śląsk/Silesia and the process through which it entered the collective consciousness. The Piast dynasty was a significant element of this tradition, considering the attempts made at preserving their memory, primarily within historiographical works. Saint Hedwig of Silesia (d. 1243) was of particular significance to this dynasty; her cult changed from one dynastic in nature into regional, as she became the patron saint of Silesia. In Silesian tradition Piotr Włostowic (d. circa 1151) is another very important figure; his literary and historiographical prowess allowed him to rise to the status of regional hero. The local Church was also significant in the forging of regional identity. The author analyzed the actions it took for the purpose of preserving and strengthening knowledge about the Bishops of Wrocław, indicating such sources as the bishop catalogues which were widespread in Silesia. Much attention was paid to the regional discourse present within chronicles and other publications; in the Late Middle Ages these became the main platform for expression of regional issues. Analyzing the particulars of some events, the author indicated the tangled paths to the formation of a Silesian regional identity. This was primarily the result of the far-reaching ethnic changes taking place in Silesia at the turn of the 12th and 13th centuries, alongside the influence of cultural traits imported from bordering regions.
Keywords: Silesia; Wrocław; historiography; middle ages; regional identity; patriotism; Church; chronicles; annals; catalogues of bishops; Piast dynasty; St. Hedwig of Silesia; Henryków Book; German language; Polish language; Latin